2017
DOI: 10.1111/jcmm.13290
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein A‐I mimetic peptide, D‐4F, restrains neointimal formation through heme oxygenase‐1 up‐regulation

Abstract: D‐4F, an apolipoprotein A‐I (apoA‐I) mimetic peptide, possesses distinctly anti‐atherogenic effects. However, the biological functions and mechanisms of D‐4F on the hyperplasia of vascular smooth muscle cells (VSMCs) remain unclear. This study aimed to determine its roles in the proliferation and migration of VSMCs. In vitro, D‐4F inhibited VSMC proliferation and migration induced by ox‐LDL in a dose‐dependent manner. D‐4F up‐regulated heme oxygenase‐1 (HO‐1) expression in VSMCs, and the PI3K/Akt/AMP‐activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Accumulating evidences indicated that D-4F protects endothelial cells against ox-LDL-induced injury by antagonizing the down-regulation of pigment epithelium-derived factor (PEDF) (Ding et al, 2014). We also found that D-4F alleviates ox-LDL-induced oxidative stress and promotes endothelial repair through the eNOS/HO-1 pathway (Liu et al, 2017a; Liu et al, 2017b). Furthermore, D-4F accelerates vasodilatation and restrains atherosclerosis by both regulating phospholipid metabolites and decreasing plasma long-chain lysophosphatidylcholine (LysoPC) in LDL-R null mice (Ou et al, 2012).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Accumulating evidences indicated that D-4F protects endothelial cells against ox-LDL-induced injury by antagonizing the down-regulation of pigment epithelium-derived factor (PEDF) (Ding et al, 2014). We also found that D-4F alleviates ox-LDL-induced oxidative stress and promotes endothelial repair through the eNOS/HO-1 pathway (Liu et al, 2017a; Liu et al, 2017b). Furthermore, D-4F accelerates vasodilatation and restrains atherosclerosis by both regulating phospholipid metabolites and decreasing plasma long-chain lysophosphatidylcholine (LysoPC) in LDL-R null mice (Ou et al, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…Human umbilical vein endothelial cells (HUVECs) were isolated by collagenase-based digestion of umbilical veins from healthy donors (Liu et al, 2017a; Liu et al, 2017b). HUVECs were cultured in gelatin-coated polystyrene dishes with endothelial cell medium (ECM) supplemented with 5% fetal bovine serum (FBS) and endothelial cell growth supplement (ECGS) in an incubator with 5% CO 2 at 37°C (Liu et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the work of Liu et al ( 2017b ) showing that D-4F inhibited vascular smooth muscle cells (VSMC) proliferation and migration in vitro and neointimal formation in vivo through heme oxygenase-1(HO-1) up-regulation. Authors' conclusions further demonstrate that HO-1 represents a druggable target for vascular injury prevention and that D-4F may be exploited as a safe and effective treatment to induce HO-1 into a clinical setting.…”
mentioning
confidence: 99%